The Giving Tree - Silverstein, Shel. (New York : HarperCollins, 2004)
A young boy grows to manhood and old age experiencing the love and generosity of a tree which gives to him without thought of return.
Accelerated Reader AR
Reading Counts RC
Accelerated Reader
Keywords: Generosity; Juvenile fiction; Trees; Juvenile fiction; Sacrifice; Juvenile fiction; Romance fiction; Sound recordings; Romance fiction; Audiobooks; Childrens audiobooks; Fiction; Juvenile works; Sound recordings; Fiction